2020
DOI: 10.1589/jpts.32.323
|View full text |Cite
|
Sign up to set email alerts
|

Perception of tertiary care clients toward the availability of physical therapy service at primary health care centers in Saudi Arabia: a cross-sectional survey

Abstract: To explore the views of clients referred for physical therapy in a tertiary care setting regarding the integration of physical therapy service at primary health care centers. [Participants and Methods] A selfadministered questionnaire was distributed to eligible Saudi clients. The questionnaire consisted of three sections including demographic information section; closed-ended section with 6 Likert scale items on the perceptions of potential advantages of physical therapy service at the primary health care lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, there is an agreement among patients and stakeholders that physical therapy services are best suited to the primary care setting [19,20] and physical therapy will soon be integrated into the primary care setting. Moreover, various studies from different countries have demonstrated successful implementation of physical therapy at the first point of contact for patients with musculoskeletal conditions [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an agreement among patients and stakeholders that physical therapy services are best suited to the primary care setting [19,20] and physical therapy will soon be integrated into the primary care setting. Moreover, various studies from different countries have demonstrated successful implementation of physical therapy at the first point of contact for patients with musculoskeletal conditions [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The role of physiotherapists is most crucial when it comes to the health of the people as these personnel director guide the people about how to manage their health issues [14]. These days, health issues have remained the major concern for the people while physiotherapists usually help the people about maintaining their health by proper and suitable kind of exercise as well as other aspects that are needed for a person to maintain health to the highest level [9]. The physiotherapists spend their lives to keep interacting with the people and listening to their health issues, and then directing them to buy medicines that are more likely to resolve their health issues.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In this way, it is the physiotherapists who usually keep the public aware of the disease attacks and advise the public to take the further step to make their body immune to various diseases. The education and advice of the physiotherapists are also critical and greatly contribute to people's health by preventing and even managing the diseases [9].…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation